2000
DOI: 10.4319/lo.2000.45.5.1030
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish as geomorphic agents and ecosystem engineers: Biological behavior affects sand and gravel erosion in experimental streams

Abstract: Effects of animals on the transport of solids (e.g., sediments) can modify earth-surface processes and landforms (role as geomorphic agents) and resources for other organisms (role as ecosystem engineers). Therefore, we studied the impact of crayfish (Orconectes limosus) behavior on sand-gravel erosion and bottom habitat over riffle-pool sequences in experimental streams. We manipulated the availability of crayfish food and refugia. Refugia availability had clear effects on overall crayfish activity. The estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
158
4
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 45 publications
3
158
4
6
Order By: Relevance
“…Third, it should be noted that our experiment was limited to three fish species, thus neglecting other fish that are known to be active streambed sediments bioturbators either by feeding or swimming (e.g., the barbel Barbus barbus L.1758: Pledger et al, 2014; the gudgeon Gobio gobio L.1758: Statzner et al, 2003b;Statzner and Sagnes, 2008;larval lamprey: Shirakawa et al, 2013) or nest digging (e.g., salmonids: De Vries, 2012), but also other zoogeomorphic animals such as crayfish (e.g., Statzner et al, 2000) or benthic macro-invertebrates (e.g., De Nadaı¨- Monoury et al, 2013). Moreover, due to limited space, a single fish was placed into each aquarium preventing all complex biotic interactions known to affect bioturbating activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, it should be noted that our experiment was limited to three fish species, thus neglecting other fish that are known to be active streambed sediments bioturbators either by feeding or swimming (e.g., the barbel Barbus barbus L.1758: Pledger et al, 2014; the gudgeon Gobio gobio L.1758: Statzner et al, 2003b;Statzner and Sagnes, 2008;larval lamprey: Shirakawa et al, 2013) or nest digging (e.g., salmonids: De Vries, 2012), but also other zoogeomorphic animals such as crayfish (e.g., Statzner et al, 2000) or benthic macro-invertebrates (e.g., De Nadaı¨- Monoury et al, 2013). Moreover, due to limited space, a single fish was placed into each aquarium preventing all complex biotic interactions known to affect bioturbating activities.…”
Section: Discussionmentioning
confidence: 99%
“…They could result simultaneously in waters with higher suspended solids and fine elements (e.g., organic detrital matter) concentrations, but lower fine sediment volumes (Statzner, 2012) in local places such as deposition areas. Fine sediment removal may subsequently affect negatively biological communities by reducing the establishment and presence of sessile or movement-limited insects (Pringle et al, 1993) and reducing bed biofilms (Statzner et al, 2000) that indirectly affect leaf decomposition processing. In lentic waters, turbidity could be hastened and concentrations in nutrients and organic material higher due to the resuspension of sediments to the water column through bioturbation by fish (e.g., Breukelaar et al, 1994;Matsuzaki et al, 2009), resulting subsequently in phytoplankton blooming and water eutrophication, already enhanced by warming (Jeppesen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioturbation is known to affect ecosystem function in marine ecosystems, but, recently, it has received attention in stream and river ecosystems (Moore 2006). Studies of freshwater aquatic ecosystems in various biomes have identified nocturnal species of macroinvertebrates and amphibians as drivers of bioturbation (Zanetell and Peckarsky 1996;Statzner et al 2000). Predaceous stoneflies increase sediment suspension from the streambed while searching the rocks and sediments for prey (Zanetell and Peckarsky 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Les chaînes alimentaires y sont en effet très courtes et la faune amphidrome représente la majorité de la biomasse (COVICH et McDOWELL, 1996 ;PRINGLE, 1997). De part leurs diverses activités (bioturbation, alimentation, déplacements), certaines crevettes et certains poissons ont un effet spectaculaire sur la biomasse d'algue, sur la structure des communautés notamment celles d'insectes ainsi que sur le transport solide des particules fines (rôle d'organismes ingénieurs sensus JONES et al, 1994 ;STATZNER et al, 2000) (CHACE et HOBBS, 1969 ;PRINGLE et al, 1993 ;PRINGLE et BLAKE, 1994 ;PRINGLE, 1996 ;PRINGLE et HAMAZAKI, 1997). La conservation de la faune amphidrome en amont des ouvrages est donc essentielle pour garantir l'intégrité des écosystèmes aquatiques (PRINGLE et SCATENA, 1999a), gage d'une eau de bonne qualité (YOUNG et al, 1994).…”
Section: Intérêts De La Conservation Des Espèces Considéréesunclassified